UNTOUCHABLE BEAUTY OF EVERYDAY AESTHETICS IN WIM WENDERS’ PERFECT DAYS - Fatmawati, Nindya Galuh; Saraswati, Agni (Paradigma: Jurnal Kajian Budaya, 2025)
Wim Wenders, in his latest film Perfect Days (2023), presents an everyday aesthetic experience conveyed through a visually striking aesthetic characterized by a "peaceful" gaze. This study aims to explore the everyday aesthetics depicted in Perfect Days, which align with traditional Japanese aesthetics, specifically wabi-sabi. The analysis is framed using Todd McGowan's Cinema of Desire theory. The research employs a qualitative descriptive method to examine the subject and utilizes a Psychoanalytic approach for analysis. The findings reveal that object ‘a’ in Perfect Days is highlighted through mise-en-scène and music, as these two cinematic elements facilitate a moment of reconnecting with lost desire. The everyday aesthetics and object a in the film can be categorized into three key areas that convey meaning and represent various desires: the beauty of time, the romance of trauma and loss, and the absence of material drives.